2020
DOI: 10.20517/2394-4722.2020.77
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-induced severe bullous pemphigoid in a patient with renal cancer: a case report and literature review

Abstract: With the widespread use of immunotherapy in numerous solid tumours, immunotherapy-related adverse events (irAEs) have started to emerge and bring new challenges for clinicians to manage. Among established irAEs, dermatologic toxicity is one of the most common toxicities; it is often mild but can be severe and potentially life-threatening, such as bullous pemphigoid. Here, we report a case of nivolumab-mediated severe, extensive, refractory bullous pemphigoid involving both skin and oral mucosa in a patient wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Often, mild and localized pruritus is the only clinical symptom before quickly progressing to hemorrhagic blisters on the chest, abdomen, thighs, and upper arms. 9 The average time to diagnosis in nine reported cases was 9.4 months. 12 A review of 21 cases with PD‐1‐induced BP found that nine were associated with nivolumab in which the median time to cutaneous toxicity and bullae formation was 12 weeks.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Often, mild and localized pruritus is the only clinical symptom before quickly progressing to hemorrhagic blisters on the chest, abdomen, thighs, and upper arms. 9 The average time to diagnosis in nine reported cases was 9.4 months. 12 A review of 21 cases with PD‐1‐induced BP found that nine were associated with nivolumab in which the median time to cutaneous toxicity and bullae formation was 12 weeks.…”
Section: Discussionmentioning
confidence: 94%
“…Increasing usage of immunotherapy for cancer management has resulted in an increased incidence of BP as a cutaneous toxicity. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While most of these side effects are mild to moderate in severity, some manifestations can progress to high-grade and potentially life-threatening situations - such as bullous pemphigoid. [ 3 , 4 ] Since 2015, more than 40 cases of immunotherapy-related BP have been reported, involving either the skin or mucous membrane. Of these case reports, only 1 described the development of BP following concomitant use of both nivolumab and RT.…”
Section: Introductionmentioning
confidence: 99%